Targeting our Blind Spot: A Metacognitive Intervention Ameliorates Negative Feelings, Evaluations, and Stereotypes Towards Conservatives in a Liberal Sample - Klaus Michael Reininger; Nora Rebekka Krott; Margret Hoenisch; Jakob Scheunemann; Steffen Moritz (Journal of Social and Political Psychology, 2020)
Political polarization between conservatives and liberals threatens democratic societies. Ameliorating liberal research participants’ negative feelings, evaluations, and stereotypes towards conservatives might be one step into the direction of a political depolarization. In a sample of U.S.-American liberal research participants recruited via Amazon’s Mechanical Turk (N = 271), we randomly assigned participants in a pre-post-design either to a clinical-psychological, metacognitive-intervention (MCT), an educational, or a no-treatment-no-pre-measurement-control-condition. In the MCT-condition, participants were first asked seemingly simple questions that frequently elicited incorrect responses, followed by corrective information. In the educational condition, information was conveyed in a simple narrative form. MCT was significantly more effective in ameliorating liberal participants’ negative feelings, evaluations, and stereotypes towards conservatives compared to the other two control-conditions. Further, MCT-participants significantly reduced their negative feelings, negative evaluations, and perceptions of threat from pre- to post-measurement, significantly more than participants in the educational condition. The results of our preliminary study and its implications are discussed, and recommendations for further research are made.